Advances in emerging drugs for the treatment of neuroblastoma. (2nd January 2017) - Berlanga, Pablo; Cañete, Adela; Castel, Victoria
ABSTRACT: Introduction: Neuroblastoma is the most common solid extracranial tumor of childhood. Outcome for children with high-risk neuroblastoma remains suboptimal. More than half of children diagnosed with high-risk neuroblastoma either do not respond to conventional therapies or relapse after treatment with dismal prognosis. Areas covered: This paper presents a short review of the state of the art in the current treatment of high-risk neuroblastoma. An updated review of new targeted therapies in this group of patients is also presented. Expert opinion: In order to improve prognosis for high-risk patients there is an urgent need to better understand spatial and temporal heterogeneity and obtain new predictive preclinical models in neuroblastoma. Combination strategies with conventional chemotherapy and/or other targeted therapies may overcome current ALK inhibitors resistance. Improvement of international and transatlantic cooperation to speed clinical trials accrual is needed.